The Impact of Inflammation and Immune Activation on B Cell Differentiation during HIV-1 Infection - Ruffin, Nicolas; Hong Pham, Thang; Rethi, Bence; Nilsson, Anna; Chiodi, Francesca (Frontiers in Immunology, 2012)
HIV-1 infection is characterized by continuous antigenic stimulation, chronic immune activation and impaired survival of T and B cells. A decline of resting memory B cells has previously been reported to occur in both children and adults infected with HIV-1; these cells are responsible for mounting and maintaining an adequate serological response to antigens previously encountered in life through natural infection or vaccination. Further understanding of the mechanisms leading to impaired B cell differentiation and germinal center reaction might be essential to design new HIV vaccines and therapies that could improve humoral immune responses in HIV-1 infected individuals. In the present article we summarize the literature and present our view on critical mechanisms of B cell development which are impaired during HIV-1 infection. We also discuss the impact of microbial translocation, a driving force for persistent inflammation during HIV-1 infection, on survival of terminally differentiated B cells and how the altered expression of cytokines/chemokines pivotal for communication between T and B cells in lymphoid tissues may impair formation of memory B cells.